2017
DOI: 10.1007/s11250-017-1413-6
|View full text |Cite
|
Sign up to set email alerts
|

Predicting early pregnancy in Egyptian buffalo cows via measuring uterine and luteal blood flows, and serum and saliva progesterone

Abstract: Various methods are being employed to detect early pregnancy in domestic animals. This study aimed to predict early pregnancy in buffaloes via measuring the corpus luteum (CL) diameter, the luteal blood flow (LBF) area, the uterine blood flow (UBF) vascularization area, and progesterones in saliva and serum for non-pregnant (NPBs, N = 12) and pregnant (PBs, N = 12) buffaloes. The results revealed that the CL diameter and the luteal color blood flow blue and red (P = 0.0001) areas of the pregnant animals kept i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 33 publications
3
14
0
2
Order By: Relevance
“…In our study, pregnant buffaloes showed, at Day 10 post-AI, higher BFA and P 4 blood concentration (P < 0.01) but not higher CLS compared to their not-pregnant counterparts. This latter finding is in agreement with another study (13), in which no differences in the CL area were recorded during this period (Day 5-10) between pregnant and not-pregnant buffaloes. It is already known that, since Day 5 post-TAI, buffaloes that showed lower CL vascularization had a lower pregnancy rate (7).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, pregnant buffaloes showed, at Day 10 post-AI, higher BFA and P 4 blood concentration (P < 0.01) but not higher CLS compared to their not-pregnant counterparts. This latter finding is in agreement with another study (13), in which no differences in the CL area were recorded during this period (Day 5-10) between pregnant and not-pregnant buffaloes. It is already known that, since Day 5 post-TAI, buffaloes that showed lower CL vascularization had a lower pregnancy rate (7).…”
Section: Discussionsupporting
confidence: 93%
“…The color Doppler ultrasound imaging approach has the potential to improve buffalo reproductive efficiency by allowing for earlier resynchronization of open females and, consequently, a reduction in the interval between services (5,13). Moreover, the use of a free post-processing tool such as ImageJ could be of great advantage for management strategies that use intensive resynchronization schedules to improve reproductive performance.…”
Section: Introductionmentioning
confidence: 99%
“…While in some studies, pregnant buffaloes showed a higher CL area compared to nonpregnant subjects [ 10 , 27 ], no differences were observed in other studies [ 28 , 29 ]. In a recent trial [ 30 ], a difference in CL dimensions between pregnant and nonpregnant buffaloes was observed only 14 days after insemination, while no differences were recorded during the Day 5 to Day 10 period. Therefore, further investigations are needed to clarify this aspect.…”
Section: Discussionmentioning
confidence: 99%
“…The left panel is by B-mode ultrasonography (A, C, E, G), while the right panel is representing the color (B, F) and power Doppler modes (D, H).). Color and power Doppler images were analyzed for the blood flow perfusions area (s) in pixels using an image analysis program (Adobe Photoshop CC software, Adobe Systems, USA) as described in buffaloes [13]. Blood flow which is colored either blue (away from the transducer) or red (toward the transducer), and total color, and power areas were counted.…”
Section: Methodsmentioning
confidence: 99%